Pengaruh Kualitas Pelayanan Fiskus dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak dalam Membayar PBB-P2 di Nagari Tanjung Barulak - Ulfa Nur Azizah; Boni Saputra (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
Taxpayer compliance remains a structural challenge in Indonesia, as reflected in the national tax-to-GDP ratio, which reached only 10.07% in 2024. At the local level, Nagari Tanjung Barulak recorded that 650 out of 3,048 registered taxpayers had not paid their Rural and Urban Land and Building Tax (PBB-P2) in the same year, thus necessitating an in-depth empirical study of its determinants. This study aims to analyze the influence of tax administration service quality and taxpayer awareness both individually and simultaneously on taxpayer compliance in paying PBB-P2 in Nagari Tanjung Barulak. The study employed an associative quantitative approach with 100 respondents drawn from a population of 3,048 taxpayers using Slovin sampling. A validated instrument was used to measure five dimensions of service quality, three indicators of awareness, and three indicators of compliance, which were analyzed using multiple linear regression with SPSS 27. The results indicate that the quality of tax officials’ service (t = 14.049) and taxpayer awareness (t = 11.559) have a positive and statistically significant partial effect (p < 0.01), as well as a statistically significant simultaneous effect (F = 106.182; p < 0.01) with an adjusted R² of 0.681. These findings highlight the importance of a two-pronged strategy for the Nagari Government and the Tanah Datar Regency Bappenda: strengthening the responsiveness of tax collectors and conducting ongoing outreach on the function of taxes, in order to effectively improve compliance with the PBB-P2.